Wound complication after venaseal closure of incompetent perforator veins - Vlatko Cvetanovski; Dina Cimeshikj; Marija Cvetanovska; Jovanovski Jovan; Borislav Kondov (Peytchinski Publishing Ltd, Pleven, Bulgaria, 2024)
Chronic Venous Insufficiency (CVI) and venous ulceration is a common health problem causing significant patient morbidity. Apart from the chronic physical and psychological disability caused to the individual, it also results in an enormous economic burden to the health care administration. Global prevalence rates of CVI are variable but may be as high as 40% among females and 17% among males [1]. The new minimally-invasive techniques for treating CVI are steadily acquiring dominance, due to their simplicity, efficiency and low complication rate. Venaseal closure procedure is a relatively new technique that involves intravenous glue application via catheter for creating permanent seal in the vein. Its simplicity and efficiency nas made it a very attractive choice for the treating physicians, as well as the patients. However, multiple studies have reported few different types of adverse reactions cause by the adhesive nbutyl cyano-acrylate (NBCA). We are presenting the case of a 44-year-old male with severe postprocedural granulomatous reaction after Venaseal closure of bilateral crural perforator veins, leading to a necessary surgical intervention for removal of the material and prolonged wound treatment.
Keywords: chronic Venous Insufficiency; crural perforator veins; wound complication